Surgery of Motor Eloquent Glioblastoma Guided by TMS-Informed Tractography: Driving Resection Completeness Towards Prolonged Survival - Weiss Lucas, Carolin; Faymonville, Andrea Maria; Loução, Ricardo; Schroeter, Catharina; Nettekoven, Charlotte; Oros-Peusquens, Ana-Maria; Langen, Karl Josef; Shah, N. Jon; Stoffels, Gabriele; Neuschmelting, Volker; Blau, Tobias; Neuschmelting, Hannah; et al. (Frontiers in Oncology, 2022)
Background: Surgical treatment of patients with glioblastoma affecting motor eloquent brain regions remains critically discussed given the risk-benefit dilemma of prolonging survival at the cost of motor-functional damage. Tractography informed by navigated transcranial magnetic stimulation (nTMS-informed tractography, TIT) provides a rather robust estimate of the individual localisation of the corticospinal tract (CST), a highly vulnerable structure with poor functional reorganisation potential. We hypothesized that by a more comprehensive, individualised surgical decision-making using TIT, tumours in close relationship to the CST can be resected with at least equal probability of gross total resection (GTR) than less eloquently located tumours without causing significantly more gross motor functional harm. Moreover, we explored if the completeness of TIT-aided resection translates to longer survival. Methods: 61 patients (median age 63 years, m=34) with primary glioblastoma neighbouring or involving the CST were operated between 2010-2015. TIT was performed to inform surgical planning in 35 of the patients (group T; vs. 26 control patients). To achieve largely unconfounded group comparisons for each co-primary outcome (i.e., gross-motor functional worsening, GTR, survival), (i) uni- and multivariable regression analyses were performed to identify features of optimal outcome prediction; (ii), optimal propensity score matching (PSM) was applied to balance those features pairwise across groups, followed by (iii) pairwise group comparison. Results: Patients in group T featured a significantly higher lesion-CST overlap compared to controls (8.7±10.7% vs. 3.8±5.7%; p=0.022). The frequency of gross motor worsening was higher in group T, albeit non-significant (n=5/35 vs. n=0/26; p=0.108). PSM-based paired-sample comparison, controlling for the confounders of preoperative tumour volume and vicinity to the delicate vasculature of the insula, showed higher GTR rates in group T (77% vs. 69%; p=0.025), particularly in patients with a-priori intended GTR (87% vs. 78%; p=0.003). This translates into a prolonged PFS in the same PSM subgroup (8.9 vs. 5.8 months; p=0.03), with GTR representing the strongest predictor of PFS (p=0.001) and OS (p=0.0003) overall. Conclusion: The benefit of TIT-aided GTR seems to overcome the drawbacks of potentially elevated motor functional risk in motor eloquent tumour localisation, leading to prolonged survival of patients with primary glioblastoma close to the CST.